“PLEASE LEAVE A MESSAGE”: THE MEDIA ECOLOGY OF RUBEN ÖSTLUND’S PLAY, FORCE MAJEURE, AND THE SQUARE - Lynch, John (The Nordic Journal of Aesthetics, 2018)
This article examines three films by the Swedish director Ruben Östlund: Play (2011), Force Majeure (2014), and The Square (2017). It describes the role of mobile phones in the films, both on the level of content and in terms of aesthetics. Within the films, the failure of the phone to connect the protagonists to significant others is seen as symbolic of an alienation that leads them to points of crisis. Here, the mobile phone works as a device in two ways. First, as a significant communication technology, and second, as a plot contrivance to advance the dramatic conflict. Critically, the mobile phone opens an uncertain space where subjectivity becomes increasingly insecure, precisely as it becomes fundamentally intertwined with it. There is a cinematic tradition of mobilizing this ambiguity to which this process can be connected. Further, the form of these works is considered in relation to the notion of traumatic repetition, and how this expands into the wider contemporary image-culture and the key influence of YouTube within this. Here, the films are considered in relation to the changing dynamic of the public sphere in the light of the mobile recording capabilities, that have come to shape an emergent cinematic aesthetic evident in these films.